Peranan Motivasi Berprestasi, Budaya Keluarga dan Perilaku Mengajar Guru terhadap Prestasi Belajar PAI - Kurniawati Kurniawati (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
In order to obtain the learning achievements of Islamic Religious Education, a number of factors play an important role on students. The study of this thesis examined whether there was an influence of achievement motivation, family culture and teaching behavior of teachers on the student achievements of Islamic Religious Education at SMA Negeri (public senior high school) 2 Sabang. The study employed a quantitative descriptive research method, a method whose problem solving process concerning on a current research subject or object described in; the total samples were 63 students, consisting of the independent variables: achievement motivation (X1), family culture (X2), teachers’ teaching behavior (X3), and the dependent variable: learning achievements (Y). The research findings showed that there was no significant influence on the students’ learning achievements of Islamic Religious Education, with the value of r = -0.090, between variable X1 with variable Y, indicating a weak or non linear correlation. Further, it also showed that family culture (X2) did not give a significant effect on Y with r = -0.158. Similarly, the teachers’ teaching behavior (X3) with Y amounted to r = -0.001 which referred to a weak correlation or non linear and negative correlation. It can be concluded that the students’ learning achievements of Islamic Religious Education of SMA Negeri 2 Sabang were not fully influenced by these three variables.